Discourse analysis : a resource book for students - Jones, Rodney H. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Revised and updated throughout, the new edition of Discourse Analysis provides a comprehensive overview of the major approaches to and methodological tools used in discourse analysis"--
Keywords: Discourse analysis; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Linguistics